Cancer and neurotransmitter receptors - Xiaoqiang Wang; Muyan Shi; Jie Tian; Weifeng Yu; Jing Ni (Chinese Medical Journal)
Abstract. In recent years, growing evidence indicates that the nervous system plays an indispensable role in tumor development and metastasis. Elucidating crosstalk between the nervous system and tumor progression has thrived as a hot topic and a new direction for understanding cancer pathogenesis. Notably, many novel discoveries have suggested that neurotransmitter receptors (NRs) are not only widely expressed in cancer cells, but also play key roles in regulating cancer initiation and progression by diverse approaches. In this review, we summarized the latest advance in cancer neuroscience, especially emphasizing the important roles of different NRs in cancer development and prevention. The exemplary studies presented herein illustrate the emerging view that NRs are profoundly influential, manifested in tumor growth, apoptosis, angiogenesis, metastasis, resistance to drugs, and participate in the formation of neural–cancer interactions. In addition, NRs also regulate cellular metabolic processes and tumor microenvironment (TME) remodeling. More importantly, numerous basic and clinical studies have suggested that NRs may be potential targets for cancer treatments, and corresponding agonists or antagonists have been identified effectively in controlling tumor growth and metastasis. In conclusion, NRs are emerging as novel targets for anti-cancer drug exploration and clinical cancer treatments, while trying to uncover deeper mechanisms and connections between NRs and cancer is of high clinical significance and translational value.